Revisiting Dipole-Induced Fluorinated-Anion Decomposition Reaction for Promoting a LiF-Rich Interphase in Lithium-Metal Batteries - Liu Wang; Jiahui Guo; Qi Qi; Xiaotong Li; Yuanmeng Ge; Haoyi Li; Yunfeng Chao; Jiang Du; Xinwei Cui (Nano-Micro Letters)
Highlights Single-layer graphdiyne on MXene (sGDY@MXene) heterostructure was fabricated and integrated into polypropylene separators, directing a LiF-rich solid electrolyte interphase and long-term stability of lithium-metal anode. Instead of direct electron transfer from surface polar groups to fluorinated anions, the adsorbed Li ions on sGDY@MXene act as dynamic bridges collaboratively connecting the electron-donating heterostructure to the anion and its derivatives, facilitating interface charge transfer. Dedicate balance between lithiophilicity and high Li-ion mobility is the key to promote the dipole-induced fluorinated-anion decomposition.